The PERFORM-P (Principles of Evidence-based Reporting in FORensic Medicine-Pathology version). (October 2021) - Meilia, P.D.I.; Herkutanto,; Atmadja, D.S.; Cordner, S.; Eriksson, A.; Kubat, B.; Kumar, Adarsh; Payne-James, J.J.; Rubanzana, W.G.; Uhrenholt, L.; Freeman, M.D.; Zeegers, M.P.
Highlights: The PERFORM-P provides recommendations for reporting in forensic pathology. The PERFORM-P was developed using input from 106 forensic pathologists from 41 countries. The PERFORM-P consists of 61 items to be included in a forensic pathology report. The PERFORM-P is accompanied by an explanation and elaboration document. The PERFORM-P is applicable to a variety of forensic pathology cases. Abstract: Introduction: Most findings of forensic pathology examinations are presented as written reports. There are currently no internationally accepted recommendations for writing forensic pathology reports. Existing recommendations are also varied and reflect the differences in the scope and role of forensic medical services and local settings in which they are to be implemented. The legal fact-finder thus faces wide variation in the quality of forensic pathology reports, which poses a threat to the reliability of legal decision-making. To address this issue, the development of the "PERFORM-P (Principles of Evidence-based Reporting in FORensic Medicine-Pathology version)" was undertaken. The goal of the PERFORM-P is to provide common practice recommendations adaptable to local requirements to promote evidence-based practice (EBP) in forensic pathology. Methods: An international consensus study was conducted in three phases by (1) developing a long-list of items to be considered in the reporting recommendations, (2) conducting a Delphi process (an iterative survey method to transform individual opinions into group consensus) with international forensic pathologists, and (3) designing the PERFORM-P prototype and its accompanying manual. Results: With assistance from 106 forensic pathologists/forensic medical practitioners from 41 countries, the PERFORM-P was developed. The PERFORM-P consists of a list of 61 items to be included in a forensic pathology report, which is accompanied by its Explanation and Elaboration (E&E) document. Discussion: To prepare forensic pathology (postmortem) reports that incorporate principles of evidence-based practice, internationally accepted recommendations might be helpful. The PERFORM-P identifies recommendations for necessary elements to include in a forensic pathology report. PERFORM-P can be applied to a wide range of matters requiring forensic pathological analysis, acceptable to forensic pathologists from a representative selection of jurisdictions and medico-legal systems.